ChatGPT For Positive Impact? Examining the Opportunities and Challenges of Large Language Models in Education - Sain, Zohaib Hassan; Chanda Chansa Thelma; Hasan Baharun; Agatha Cryssandra Pigesia (International Journal of Educational Development, 2024)
Researchers argues that large language models are critical to the advancement of artificial intelligence and will play a vital role in future progress. Despite criticism and occasional bans, these models are persistent and poised to continue. This analysis delves into the potential benefits and challenges of utilising extensive language models in education, considering perspectives from both students and educators. These models' current status and applications are briefly reviewed, emphasising their use in generating educational material, increasing student engagement, and personalising learning experiences. The discussed challenges include the need for educators and students to develop skills and literacies to understand and navigate the technology and its limitations. Employing a strategic and pedagogical approach that stresses critical thinking and fact-checking is a crucial component of effectively integrating these models into educational institutions. AI applications in education often encounter additional challenges, including potential biases, the necessity for ongoing human oversight, and the risks of misuse. However, these challenges may present educational opportunities for students to become familiar with social biases, complexities, and risks associated with AI. The essay presents solutions for effectively addressing these challenges to ensure the responsible and ethical use of large language models in education.